Alterações sistêmicas e cardiacas após envenenamento experimental por cobra coral Micrurus frontalis em cobaias (Cavia porcellus). - Marthin Raboch Lempek (2018)
Micrurus frontalis is one of the main snakes responsible for elapidic accidents in humans in Brazil, however rare cases are described in the veterinary literature. Its venom is known for its high toxicity, with every elapic accident being considered serious. The venom is composed of three fractions: three finger toxin (3FTx), phospholipase A2 and metalloproteases. Its main action is neurological, leading to flaccid paralysis of the victims and consequently death due to respiratory insufficiency. However, there is no description in the literature of its activity in the cardiovascular system. For this reason, this study evaluates the cardiac alterations of the venom of M. frontalis in the experimental envenomation of Cavia porcellus. Twelve animals were distributed in two groups (n = 6), denominated venom group and control group. Animals of the venom group received a dose of 0.45 g / g live weight of venom of M. frontalis diluted in 0.2 ml of PBS / BSA intramuscularly (IM), while the control group received 0.2 ml of PBS / BSA IM. The electrocardiogram (ECG), Doppler echocardiogram (ECO) and blood profile were performed in two moments; time zero (T0) and two hours after the envenomation, final time (FT). After FT, the animals were euthanized, necropsied and collected for optical and electron microscopy. The ECG revealed the presence of arrhythmias, ventricular extrasystoles, in 100% of the envenoming animals. The ECO showed a negative inotropic effect of the venom of M. frontalis on the cardiac musculature, reducing approximately 25% of the cardiac ejection fraction, as well as vasoconstriction of the aortic artery and increased pulmonary artery flow. In the cardiovascular biochemical profile, a significant increase of troponin I and creatine kinase MB in FT of the envenomed animals was observed. The activated partial thromboplastin time and the D-dimer were decreased, in the FT in the envenomed group. It was concluded that the venom of M. frontalis has cardiotoxic and arrhythmogenic activity. In addition to causing heart damage, the venom acts, causing a negative inotropic effect on the heart.